2021
DOI: 10.17219/acem/131219
|View full text |Cite
|
Sign up to set email alerts
|

Notch pathway activation promotes the differentiation of beagle dog periodontal ligament stem cells to Schwann cells

Abstract: Background. Periodontal ligament stem cells (PDLSCs) have demonstrated the potential for differentiation into many cell types, though the molecular mechanism of their neural differentiation in particular remains largely unknown.Objectives. The Notch signaling pathway plays a key role in regulating cell differentiation and development.In this article, we explore its potential role in the differentiation of PDLSCs to Schwann cells (SCs). Materials and methods.The PDLSCs were either transfected with viral vectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that Notch is quite important for the maintenance of the biological properties of PDLSCs, as well as for terminal osteogenic differentiation and wound healing [10,11] . Previous literature has shown [12][13][14] that although the Notch signalling pathway is involved in the differentiation process of bone formation in PDLSCs, the mechanism of action of the Notch pathway in the osteogenic differentiation of PDLSCs is unclear. Studies have shown that periodontal stem cells express Notch1 [15,16] and that the behaviour of stem cells can be regulated by cellular and molecular cues from their microenvironment [16][17][18] .…”
Section: The Notch Signalling Pathwaymentioning
confidence: 99%
“…Studies have shown that Notch is quite important for the maintenance of the biological properties of PDLSCs, as well as for terminal osteogenic differentiation and wound healing [10,11] . Previous literature has shown [12][13][14] that although the Notch signalling pathway is involved in the differentiation process of bone formation in PDLSCs, the mechanism of action of the Notch pathway in the osteogenic differentiation of PDLSCs is unclear. Studies have shown that periodontal stem cells express Notch1 [15,16] and that the behaviour of stem cells can be regulated by cellular and molecular cues from their microenvironment [16][17][18] .…”
Section: The Notch Signalling Pathwaymentioning
confidence: 99%